The development of sport preference structures - Prot, Franjo (Array, 2003)
The aim of this cross-sectional study was to compare latent structures of sport preferences in urban children of different age. The research was done on four samples of 5th to 8th grade elementary school male pupils, with the total of 685 boys. The sample consisted of pupils from 3 metropolitan schools. Modal ages in four sample were11, 12, 13 and 14 years, respectively. The subjects were given the list of 52 sports to be evaluated on five-point scale during regular physical education classes. The latent structure of sport preferences of each sample was established by component analysis with promax transformation of principle axes. The PB criterion of factor extraction was used, and resulted in five factors in all four sets of data. The comparison of four factor solutions was done by the congruences of promax pattern matrix vectors. The factor analyses of four samples resulted in different solutions. Only two factors were found to be similar in all four data sets, one defined as factor of outdoor and adventurous sports, and the other defined as team sports factor with addition of tennis and table tennis. The factors obtained on 7th and 8th grade samples were mutually more congruent than compared with factors obtained on younger subjects. It was concluded that the intense phase of sport preference structure formation probably lasts few years more than expected regarding simple analyses of popularity of different sports. It is probable that more stable preference structures could be expected some years after entering adolescence.